Beautiful Quilling Step by step - Wilson, Janet; Cardinal, Judy; Crane, Diane Boden; Jenkins, Jane (London Search Press, 2010)
The beautiful work of four experienced paper crafters has been collected here, giving you all the inspiration and knowledge you could need to make your own fantastic quilled craftwork. Four experienced paper crafters show you everything you need to make your own quilled characters, wildflowers and motifs to decorate your craftwork
Arts (Papercrafts)
1
Keywords: Paper crafts